Exploring the Microbial Ecology of Nitrification Denitrification in Wastewater Treatment: Innovations and Future Directions - J, Sumitha; Konwar, Tashmi; Raj, Pranav; Nehul, Janardhan Namdeo; Hazarika, Prasanta Protim; Gangopadhyay, Sourav; Chattopadhyay, Dipanwita; Sampathkumar, T.; Sivakumar, K.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The nitrification-denitrification process serves as a critical mechanism in the biological removal of nitrogen from wastewater, a necessity for mitigating the environmental impact of nitrogen compounds on aquatic ecosystems. This complex process is orchestrated by diverse microbial communities, whose ecological interactions and functional capabilities are central to the efficiency and stability of nitrogen removal. In recent years, advances in molecular biology and microbial ecology have shed new light on the intricate dynamics within these microbial communities, revealing the roles of lesser known microbial taxa and the importance of microbial community structure and function in optimizing nitrification denitrification processes. This review provides a comprehensive examination of the microbial ecology involved in nitrification and denitrification, exploring the roles of key microbial players, including ammonia oxidizing bacteria (AOB), Nitrite oxidizing Bacteria (NOB), ammonia oxidizing archaea (AOA), and denitrifying bacteria. The review also delves into the environmental factors that influence microbial community dynamics, such as pH, temperature, oxygen availability, and the presence of inhibitory substances. By understanding these factors, the review highlights the challenges of maintaining stable and efficient nitrogen removal processes, particularly in the face of environmental fluctuations and operational disturbances, the review discusses recent innovations in wastewater treatment technologies that leverage microbial ecology to enhance process efficiency. These include bio-augmentation strategies, where specific microbial strains are introduced to bolster nitrification and denitrification, and advanced bioreactor designs, such as moving bed biofilm reactors (MBBRs) and membrane bioreactors (MBRs), which provide optimized environments for microbial growth and activity. The integration of anaerobic ammonium oxidation (anammox) processes, which offer significant energy savings and reduce greenhouse gas emissions, is also explored as a promising alternative to traditional nitrification pathways.